Song without voice: the power of the vendors song in Papa, Can You Hear Me Sing? - Goh, Yen-Lin (Tanjong Malim, 2019)
Song without voice: the power of the vendors song in Papa, Can You Hear Me Sing? by Goh, Yen-Lin